Evaluating chronic suicide risk with the Personality Assessment Inventory: Development and initial validation of the Chronic Suicide Risk Index (S_Chron). (30th November 2016) - Sinclair, Samuel Justin; Roche, Michael J.; Temes, Christina; Massey, Christina; Chung, Wei-Jean; Stein, Michelle; Richardson, Laura; Blais, Mark
Abstract: The current study sought to develop and validate a new measure of chronic suicide risk (the S_Chron ) from the Personality Assessment Inventory in a mixed sample of psychiatric inpatients and outpatients. In an initial development sample ( N =397), hierarchical logistic regression identified six PAI variables uniquely associated with multiple versus single/no prior suicide attempts after controlling for sample demographics: Negative Impression Management, Situational Stress, Mania – Grandiosity, Borderline – Negative Relationships, Borderline – Self-Harm, and Antisocial Behaviors. These indicators were then aggregated into a single index ( S_Chron ) and evaluated in terms of validity in an independent clinical sample ( N =398). Results indicated the S_Chron effectively differentiated between groups with multiple versus single/no prior suicide attempts, even after controlling for the effects of the PAI Suicidal Ideation (SUI) and Suicide Potential (SPI) indices, with moderate to large effect sizes observed (range of Cohen's d's =0.30–0.91). Further, the S_Chron incremented all other PAI indices and SUI in predicting multiple suicide attempts. The potential clinical application and ways in which the S_Chron may augment other existing measures of suicide risk are discussed. Highlights: This study developed a new measure of chronic suicide risk (the S_Chron ) from the Personality Assessment Inventory (PAI). Six PAI variables uniquely associated with multiple versus single / no prior suicide attempts were aggregated into a single index (i.e., the S_Chron ). In an independent sample, the S_Chron effectively differentiated between groups with multiple versus single / no prior suicide attempts. The S_Chron also incremented all other PAI indices and suicidal ideation in predicting multiple suicide attempt status. The S_Chron provides clinicians with a new tool for evaluating chronic suicide risk, augmenting other common measures of suicide.